Towards Deeper Financial Integration in Europe: What the Banking Union Can Contribute - Claudia M. Buch; Tobias Körner; Benjamin Weigert (Credit and Capital Markets – Kredit und Kapital, 2015)
The European Banking Union is a major step forward in fixing major deficiencies in the institutional framework of the Euro area. The absence of effective banking supervision and resolution powers at the European level promoted excessive private risk-taking in the up-run to the Euro crisis. Effective private risk sharing once risks materialized has been hampered. A properly designed Banking Union facilitates and improves private risk sharing, and it is thus a necessary institutional complement to a monetary union. Yet, the institutional framework of the Banking Union needs further strengthening in three regards. First, the supervisory framework needs to ensure uniform supervisory standards for all banks, including those located in non-Euro area countries. Also, conflicts of interest between monetary policy and banking supervision need to be mitigated. Second, bank resolution suffers from a highly complex governance structure. Restructuring and bail-in rules allow for a high degree of discretion at the level of the resolution authority. We propose to introduce a statutory systemic risk exception, by which the exercise of discretion would be reduced, thereby strengthening the credibility of the bail-in. Third, in order to enhance the credibility of creditor involvement, fiscal backstops and ex-ante specified cross-border burden-sharing agreements are needed. – – Der Weg zu mehr Finanzmarktintegration in Europa: Was die Bankenunion beitragen kann Die europäische Bankenunion ist ein wichtiger Schritt zur Beseitigung grundlegender Schwachstellen des institutionellen Rahmens des Euro-Raums. Im Vorfeld der Krise trugen fehlende effektive europäische Aufsichts- und Abwicklungskompetenzen für Banken zur überhöhten Risikonahme im Privatsektor bei und erschwerten dann die Risikoteilung, also die Verteilung von Verlusten, nachdem die Risiken schlagend wurden. Eine angemessen ausgestaltete Bankenunion ermöglicht und verbessert die Risikoteilung und ist eine notwendige institutionelle Ergänzung zur Währungsunion. Der institutionelle Rahmen der Bankenunion sollte allerdings in dreierlei Hinsicht gestärkt werden: Erstens muss der Aufsichtsrahmen einheitliche Aufsichtsstandards für sämtliche Banken gewährleisten, Banken in Mitgliedstaaten außerhalb des Euro-Raums eingeschlossen. Zudem müssen Interessenkonflikte zwischen Aufsicht und Geldpolitik abgemildert werden. Zweitens leidet der Bankenabwicklungsmechanismus an einer überaus komplexen Governance-Struktur. Die Regeln zur Abwicklung und Gläubigerbeteiligung belassen der Abwicklungsbehörde zu große Ermessensspielräume. Wir schlagen die Einführung einer Systemic Risk Exception vor, die die Ermessensspielräume reduzieren und das Bail-in glaubwürdiger machen würde. Drittens werden fiskalische Backstops und Lastenteilungsvereinbarungen für grenzüberschreitend tätige Institute benötigt, um die Glaubwürdigkeit der Gläubigerbeteiligung zu stärken.
Keywords: E02; E42; G18; 330; European Banking Union; Single Supervisory Mechanism; Single Resolution Mechanism; risk sharing